Impact of Capital Structure Management on Profitability of Commercial Banks in Nepal - Mallik, Anamika; Agrawal, Neha (Journal of Economics and Management, 2025)
This in-depth article examines the complex interplay between capital structure and profitability in many Nepalese commercial banks. The statistical analysis of the study incorporates secondary data. Descriptive and casual comparative analyses were performed using SPSS software, utilizing data collected from bank websites and employing correlations and multiple regression models for hypothesis testing. The study utilizes regression and correlation analysis to assess the influence of Short-term Debt Ratio (STDR), Long-term Debt Ratio (LTDR), Total Debt to Assets Ratio (TDAR), Total Debt-equity Ratio (TDER), and Return on Equity (ROE) by analysing data from various financial accounts. The results show that there are strong links between the parts of capital structure and measures of profitability. The findings from this research offer significant assistance for strategic financial decision-making, emphasizing the complex relationships that influence the interaction between capital structure decisions and business profitability among Nepalese commercial banks. There is significant relationship between STDR, LTDR, TDAR and TDER with ROA of commercial banks in Nepal.